2022
DOI: 10.3389/fcell.2022.806989
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of Two Hepatocellular Carcinoma-Progression Prognostic Scores Based on Gene Set Variation Analysis

Abstract: Background: Liver hepatocellular carcinoma (LIHC) remains a global health challenge with a low early diagnosis rate and high mortality. Therefore, finding new biomarkers for diagnosis and prognosis is still one of the current research priorities.Methods: Based on the variation of gene expression patterns in different stages, the LIHC-development genes (LDGs) were identified by differential expression analysis. Then, prognosis-related LDGs were screened out to construct the LIHC-unfavorable gene set (LUGs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, ACADL has been linked to the advancement of esophageal squamous cell carcinoma and the negative prognosis of affected individuals ( Yu et al, 2018 ). ACADL was identified as a critical gene in the development of liver hepatocellular carcinoma and is strongly associated with favorable prognosis ( He et al, 2022 ). The crucial factor determining the anti-atherogenic phenotype of dKO mice was found to be the dysregulation of ACADL ( Längst et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACADL has been linked to the advancement of esophageal squamous cell carcinoma and the negative prognosis of affected individuals ( Yu et al, 2018 ). ACADL was identified as a critical gene in the development of liver hepatocellular carcinoma and is strongly associated with favorable prognosis ( He et al, 2022 ). The crucial factor determining the anti-atherogenic phenotype of dKO mice was found to be the dysregulation of ACADL ( Längst et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…GSVA was conducted using the GSVA package (version 1.50.0), and gene sets were obtained from the Gene Set Enrichment Analysis Molecular Signatures Database. Similar to the analysis of differentially expressed proteins, statistical differences in GSVA enrichment scores between groups were obtained through moderated pairwise 2-tailed t -tests using limma ( He et al, 2022 ). Itch correlation analysis involved a correlation test for repeated measures between Worst Itch Numeric Rating Scale and cytokine plasma expression levels for a total of 9 sample points (3 baseline, 3 after treatment, and 3 healthy controls) using the rmcorr package (version 0.6.0).…”
Section: Methodsmentioning
confidence: 99%
“…In LIHC Supplementary Figure S4(B), no immune cells showed any significant survival analysis accept when cumulative survival analysis was done which in turns demonstrated that immunological infiltrates were strongly associated (p < 0.05) with B4GALNT1. At last, GISTIC 2.0 was used to characterise somatic copy number variations such as deep deletion (-2), arm-level deletion (-1), diploid/normal (0), arm-level gain (1), and strong amplification (2). In LIHC Supplementary Figure S4(C…”
Section: Analysis Of High and Low B4galnt Groups In Hepatocellular Ca...mentioning
confidence: 99%
“…The global prevalence of LIHC is rising. LIHC is common in people with cirrhosis and chronic liver disease [2]. LIHC ranks as the sixth most prevalent cancer worldwide and holds the position of the third primary factor leading to cancer-related deaths.…”
Section: Introductionmentioning
confidence: 99%